Effects of nasal lavage with and without mupirocin after endoscopic endonasal skull base surgery: a randomised, controlled study. Issue 12 (27th December 2019) - Ng, B H K; Tang, I P; Narayanan, P; Raman, R; Carrau, R L
Abstract: Background: Nasal lavage with mupirocin has the potential to reduce sinonasal morbidity in endoscopic endonasal approaches for skull base surgery. Objective: To evaluate the effects of nasal lavage with and without mupirocin after endoscopic endonasal skull base surgery. Methods: A pilot randomised, controlled trial was conducted on 20 adult patients who had undergone endoscopic endonasal approaches for skull base lesions. These patients were randomly assigned to cohorts using nasal lavages with mupirocin or without mupirocin. Patients were assessed in the out-patient clinic, one week and one month after surgery, using the 22-item Sino-Nasal Outcome Test questionnaire and nasal endoscopy. Results: Patients in the mupirocin nasal lavage group had lower nasal endoscopy scores post-operatively, and a statistically significant larger difference in nasal endoscopy scores at one month compared to one week. The mupirocin nasal lavage group also showed better Sino-Nasal Outcome Test scores at one month compared to the group without mupirocin. Conclusion: Nasal lavage with mupirocin seems to yield better outcomes regarding patients' symptoms and endoscopic findings.